Multiracialism Engineered: The Limits of Electoral and Spatial Integration in Singapore - TAN, Eugene K. B. (Institutional Knowledge at Singapore Management University, 2007)
This paper examines Singapore's innovations in electoral and spatial integration. In examining the Group Representation Constituency and the Ethnic Integration Policy, a critique is made of the official discourse that multiracialism is internalized and entrenched in Singapore's political psyche and electoral process. While the electoral and spatial integration policies are driven by the objective of enhancing multiracialism, their actual workings do not adequately advance the development of norms and values that would be truly supportive of the need for a multiracial legislature and an abiding commitment to multiracialism. The layering of the electoral system with other political objectives, such as administrative decentralization and ensuring the continued dominance of the ruling party, has undermined the effectiveness of electoral and spatial integration.